Réponses

2012-11-22T15:28:41+01:00

A = 28t-14t²+12-6t-(-6t+12)

A = 28t -14t²+12-6t+6t-12

A = -14t²+28t-6

 

Pour t = 0, A = 0

Pour t =3/7

A = -14*(3/7)² + 28*3/7 -6

= -14*9/49 + 84/7-6

= -126/49 + 84/7 - 6

= -126/49 + 588/49 - 294/49

= 168/49

= 24/7

2012-11-22T15:36:56+01:00

A = 28t-14t²+12-6t-(-6t+12)

A = 28t -14t²+12-6t+6t-12

A = -14t²+28t-6

 

Pour t = 0, A = 0

Pour t =3/7

A = -14*(3/7)² + 28*3/7 -6

= -14*9/49 + 84/7-6

= -126/49 + 84/7 - 6

= -126/49 + 588/49 - 294/49

= 168/49

= 24/7

c comme l'a di nullasse